Ethyl ester production from Iranian bitter almond (BAO) oil to improve the performance and emissions of OM457 diesel engine. (June 2020) - Karimi, Parisa; Najafi, Bahman; Ardabili, Sina Faizollahzadeh; Mesri-Gundoshmian, Tarahom; Ariyanfar, Leyli; Haghighatshoar, Farid
Highlights: Ethyl ester of Iranian BAO has been produced for the first time. Its effect on engine performance and emission have been considered for the first time. The results have been studied and compared with those for diesel fuel. Abstract : Biodiesel is among the biofuels. In this study, biodiesel was produced from Iranian bitter almond (BAO) oil through the transesterification process by using ethanol (BAO ethyl ester). BAO can be considered a non-edible oil, so this parameter can add to the benefits of biodiesel production. Biodiesel was prepared in two samples, containing 5 and 20 volumetric percent of biodiesel in diesel fuel respectively (B5 and B20). The tests were done based on the ECE R-85 standard. According to this standard, the engine test is performed at four loads (25%, 50%, 75%, and 100%) and two rotational speeds, 1400 rpm and 2000 rpm. These correspond to the maximum torque and power respectively. Experimental tests were run on engine performance and emissions of biodiesel fuels. The results were studied and all the parameters were compared with diesel fuel. According to the results, the maximum brake power increased (about 9.5% compared with diesel fuel) in B20, at a load of 20% and a rotational speed of 2000 rpm. Also the maximum reduction of BSFC (about 8.6% lower than diesel fuel) happened for B20 at a load of 25% and a rotational speed of 2000 rpm. Although, the brake-specific fuel consumption (BSFC) decreased at a rotational speed of 2000 rpm and all loads for both B5 and B20 compared with diesel. Regarding the effect of biodiesel on engine emissions, the emission of nitrogen oxide (NOx) at all loads for both B5 and B20 was greater than that for diesel fuel. The carbon dioxide (CO2 ) emission of the engine was lower for B5 at a rotational speed of 2000 rpm and at all loads compared with diesel fuel.